The Nexus between Income Inequality and Employment in Industry in the USA - Daniil Storchevoi (Romanian Economic Journal)
The article is devoted to the analysis of the relationship between market income inequality in the USA and the employment in the US industrial sector. The main idea of the paper is as follows: changes in the share of employment in industry is a key factor of market income inequality in the USA. A decrease in demand for industrial workers and, as a consequence, a decline in the level of employment in industry result in higher levels of market income inequality, as it is demonstrated by the regression analysis. Such a decline is, in its turn, caused by technological progress, trade liberalization, socio-economic and political features of the USA.